Werda Notary's Responsibility for the Loss of Minutes of the Deed He Made - Utami, Siska Nur (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to analyze: 1) The legal responsibility of notaries for the loss of minutes of deeds they have made. 2) Legal protection of notaries related to the deeds they have made. The approach method used in this study is the normative legal approach. This type of research is included in the scope of normative legal research. The type and source of data in this study are secondary data obtained from literature studies. The analysis in this study is qualitative. The results of the study concluded: 1) The legal responsibility of notaries for the loss of minutes of deeds they have made, namely that notaries are not responsible for the loss of minutes of deeds after the handover of the protocol to the notary receiving the protocol. Notaries are only responsible for minutes that are lost when the notary is still in office. This is because there is no obligation for notaries to remake minutes of deeds that are lost or damaged due not to the negligence of the notary providing the protocol or the notary who is in office. But this responsibility has been transferred to the recipient of the notary protocol. Therefore, the responsibility is transferred because the loss or damage of the deed is due to the negligence of the protocol holder. Notary protocol or commonly called minutes of deed if lost later. 2) Legal protection of notary's assistant related to the deed made, namely in the Notary Law there is no specific regulation regarding legal protection for notary's assistant. The form of protection required is through the existence of statutory regulations and protection from the Indonesian Notary Association (INI). The Indonesian Notary Association (INI) has a protection field, one of the tasks of which is to accompany notaries and notary assistants, within the framework of the profession with the approval of the Supervisory Board, when summoned by investigators, prosecutors or judges. There is no clarity on the time limit for notary's assistant's responsibility for the deed made, so special legal protection is needed for Notaries, especially for notaries who are no longer in office (notary assistant).Keywords: Deed; Legal; Responsibility; Werda.